2006
DOI: 10.1111/j.1600-0897.2006.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Uterine Natural Killer (NK)‐Cell Expression and Altered Placental and Serum Levels of the NK‐Cell Promoting Cytokine Interleukin‐12 in Pre‐Eclampsia

Abstract: Results show increased numbers and altered phenotype of dNK cells in pre-eclampsia, supporting the importance of these cells for a healthy pregnancy. The altered receptor expression of dNK cells together with diminished placental IL-12 expression could implicate an altered NK cell-regulation in pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 35 publications
9
72
6
Order By: Relevance
“…However, the findings contrast with those of Stallmach et al (1999) and Bachmayer et al (2006) who reported increased numbers of CD56C cells in PE decidua compared with controls. In the absence of information on the FGR status of the PE study groups in these latter studies, use of placental bed biopsy and the avidinbiotin method, which is more sensitive than the PAP method used by Stallmach et al (1999), may also partly account for the differences in uNK cell numbers.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the findings contrast with those of Stallmach et al (1999) and Bachmayer et al (2006) who reported increased numbers of CD56C cells in PE decidua compared with controls. In the absence of information on the FGR status of the PE study groups in these latter studies, use of placental bed biopsy and the avidinbiotin method, which is more sensitive than the PAP method used by Stallmach et al (1999), may also partly account for the differences in uNK cell numbers.…”
Section: Discussioncontrasting
confidence: 55%
“…Increased numbers of CD56+ uNK cells have been reported in decidua from women with pre-eclampsia compared to age matched controls (Stallmach et al, 1999;Wilczynski et al, 2003;Bachmayer et al, 2006). In contrast, in our laboratory we have demonstrated a reduction in CD56+ uNK cells in pre-eclampsia in placental bed biopsies (Scaife, Innes, Searle, Robson, Bulmer; unpublished data).…”
Section: Uterine Nk Cells In Pathological Pregnancycontrasting
confidence: 39%
“…Most of these (IL-1␤, IFN-␥, TNF-␣, IL-12, IL-4, IL-10, and IL-2) have been reported to be expressed by human trophoblasts (23)(24)(25)(26), although in a number of different treatment/culture paradigms as well as cytokine measurement techniques. The diversity among these reports, ours included, likely explains the divergence in cytokine production by trophoblast cells in culture.…”
Section: Resultsmentioning
confidence: 99%